Analisis Faktor-Faktor yang Mempengaruhi Pengembangan Sumber Daya Manusia - Irnie Victorynie; Khumaidi, Ahmad; Umat Lili Hamdani (CV. Creative Tugu Pena, 2024)
This study aims to determine what factors influence human resource development. Human resource development is very important for the sustainability of the organization. With human resource development, productivity can be increased, competitiveness and work motivation can be maintained. This study uses a literature review method. The author found that there are several factors that can influence human resource development, including internal and external factors. In addition, there are also individual factors that are also important in HR development. Human resource development (HR) is an effort to improve the quality of employees or education personnel through education and training. There are two types of HR development, namely formal and informal development which actually complement each other in an effort to improve the quality of HR